DETERMINAN INTEGRITAS LAPORAN KEUANGAN DI INDONESIA - Margareth Enrica Sebastian; Dian Purnama Sari (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2022)
This study aims to determine the impact of leverage, audit committee, growth opportunities, and litigation risk on financial statement integrity in real estate companies listed on the Indonesia Stock Exchange in period 2015-2019. The independent variable is leverage, audit committee, growth opportunities, and litigation risk and the dependent variable is financial statement integrity. The design of this research is quantitative research. The data collection method used in this study is documentation by collecting financial statements of real estate companies in period 2015-2019 obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The population in this study are 43 companies, while sample used are 41 companies with purposive sampling technique. Data analysis technique used are multiple linear regression. The results of this study showed that leverage and litigation risk has positive effect on financial statement integrity. Meanwhile, audit committee and growth opportunities has no effect on financial statement integrity.